Supplementary X-ray studies of the Ni-Sn-Bi system - Vassilev G.P.; Lilova K.I.; Gachon J.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Phase equilibria were studied in the system Ni-Sn-Bi. Special attention has been paid to the identification of the recently found ternary phase. For this purpose samples were synthesized using intimately mixed powders. After annealing and quenching, all alloys were analyzed by scanning electron microscope and by X-ray diffraction. The results give evidences about the existence of a ternary compound with approximate formula Ni6Sn2Bi to Ni7Sn2Bi. Overlapping of some neighboring diffraction peaks of this phase with NiBi and Ni3Sn_LT is the reason for the difficulties related to the X-ray diffraction identification of the ternary phase.